ASESMEN KOMPETENSI MINIMUM UPAYA DALAM MENINGKATKAN LITERASA BAHASA DAN NUMERASI DI SEKOLAH DASAR - Nana Hendra Cipta; Siti Rokmanah; Dini Nisrinawati Suhendi (STKIP Subang, 2023)
Language and numeracy literacy are the basic skills required for students to analyze reading or numbers in different contexts. Literacy and numeracy skills must be mastered and possessed in order to increase competitiveness and improve the quality of human resources. However, what happens is the low reading ability of Indonesian school children known from the results of the PISA test. In 2018, Indonesia ranked 70th out of 78 countries. Students' difficulties in critical thinking are known due to the lack of students who can solve Higher Thinking Skills (HOTS) questions and teachers who have not been able to create HOTS-based questions. Therefore, the Ministry of Education and Culture decided to implement competency assessment for all schools. The purpose of this study is to provide insight into the concept of Minimum Competency Assessment (MCA) to improve reading, writing and arithmetic skills in primary schools. The research method used is literature research. Based on the review of the literature approach, it was found that AKM focuses more on the ability to reason using language or literacy and using mathematical logic or numeracy.